Kebijakan Industri Farmasi pada Masa Pandemi COVID-19 - Meliawati, Rini (Jurnal Farmasi Udayana, 2020)
Drug shortages has been global problem since 2000s until now, and it become in serious condition by the presence of the pandemic COVID-19. The main causes of drug shortages were economic and regulation, business problem, manufacture and supply chain. During this pandemic, the main causes of drug shortages are many pharmaceutical industries closures due to quarantine, logistical problems caused by border closure, export bans, quarantine of exporting active subtances and drugs’countries, increased demand and pilling up. However, this problem has been overcome by making policies and good cooperation between governments, regulatory institution and the pharmaceutical industry throughout the world. Several policies like increasing production capacity, restrict quantity of drugs purchased by the public, facilitate the process of industrial license and making a systems such as i-SPOC (Industry Single Point of Contact).  It is expected to reduce drugs shortages problem during this pandemic.